Analysis of the Performance Management of the Activity of Political Parties in Romania - Balance Score Card for Political Organizations - Ecaterina Cornelia UNGUREANU (Dunarea de Jos University of Galati, 2021)
Given that the current political parties are going through a general period of erosion, there is a need to develop a system of performance indicators, applicable to the activity of political organizations, in order to evaluate the results of these entities. The research aims at analyzing effective management tools and techniques used in economic organizations and adapting them to the specific nature of the activity of political parties in Romania. To this end, a review of international literature and available case studies was conducted. The paper customizes the strategic model for measuring Balanced Scorecard performance, from the perspective of a political party, in order to streamline processes. The research aims to quantify the performance of a political party, by designing a balanced plan of indicators specific to a political organization. The proposed version of the model represents a real basis for performance monitoring and can be a viable alternative to the current evaluation methods used by Romanian political parties in analyzing the results of the activity.